Good Partner, Good Parent: Responsiveness Mediates the Link Between Romantic Attachment and Parenting Style. (February 2013) - Millings, Abigail; Walsh, Judi; Hepper, Erica; O'Brien, Margaret
This cross-sectional, dyadic questionnaire study examined the contribution of romantic attachment and responsive caregiving to parenting style, investigating both gender and partner effects. One hundred and twenty-five couples with children aged 7 to 8 years completed measures of attachment styles, responsive caregiving toward partner, and parenting styles. Structural Equation Modeling was used to examine the intra- and interpersonal associations between romantic attachment, caregiving responsiveness, and parenting styles. Attachment avoidance and anxiety were both negatively associated with responsive caregiving to partner, which in turn was positively associated with authoritative (optimal) parenting styles and negatively associated with authoritarian and permissive (nonoptimal) parenting styles. Responsive caregiving mediated all links between attachment and parenting, with an additional direct association between attachment anxiety and nonoptimal parenting styles that was not explained by caregiving responsiveness. Findings are discussed with reference to attachment theory.